Assessing current company reports according to the IIRC integrated reporting framework. Issue 2 (4th June 2018) - Kılıç, Merve; Kuzey, Cemil
Abstract : Purpose: This paper aims to investigate the adherence level of current company reports to the International Integrated Reporting Council (IIRC) integrated reporting framework through analysis of whether and to what extent those reports include the content elements of this framework. This study also aims to examine the impact of corporate sustainability characteristics on the adherence level of current company reports to the integrated reporting framework. Design/methodology/approach: The sample for this research comprises the non-financial companies which were listed on Borsa Istanbul, the Turkish stock exchange, as of 31 December 2015. The authors constructed a disclosure index based on the content elements of the IIRC reporting framework. They then measured the integrated reporting disclosure score (IRS) of each company through a manual content analysis of its annual reports and stand-alone sustainability reports. To test the hypotheses, the authors performed a number of statistical analyses. Findings: The authors determined that current company reports mainly present generic risks rather than company-specific; provide positive information while dismissing negative information; present financial and non-financial initiatives separately; lack a strategic focus; and include backward-looking information rather than forward-looking information. Consistent with the predictions, the authors found that the IRS is significantly and positively associated with sustainability reporting, Global Reporting Initiative (GRI) adoption, sustainability index listing and the presence of a sustainability committee. Originality/value: This study contributes to the literature by enhancing the understanding of integrated reporting practices through the application of a checklist based upon the IIRC integrated reporting framework. Further, this study contributes to the literature by evaluating the impact of corporate sustainability characteristics on IRS.